TREATMENT OF VERTICAL FRACTURE OF DISTAL RADIUS USING INTERFRAGMENTARY SCREWS THROUGH DIRECT LATERAL APPROACH TO DISTAL RADIUS - Jehan, Shah; Ahmad, Jawad (Journal of Ayub Medical College Abbottabad, 2021)
Background: Distal radius fractures are very common injuries. Majority of these fractures are transverse or oblique in nature. Isolated vertical fractures of the distal radius in the sagittal plane are rare injuries. The management of these vertical fractures is therefore different from the usual transverse or oblique fractures of the distal radius. We report on a 53-year-old right-handed gentleman who fell from his bicycle and sustained a vertical fracture of the distal radius. His distal radius fracture was fixed surgically using two interfragmentary screws. A direct lateral approach of the distal radius was used to expose the distal radius. The rationale for using direct lateral approach and interfragmentary screws for this type of fracture is discussed.